SUSTAINABLE AQUACULTURE: BRIDGING ESG PRACTICES WITH ISLAMIC VALUES IN THE DIGITAL ERA - Rustyawati, Dian; Sykriya, Wardah; Hidayatul Khabibah, Milllati (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
Tuban Regency is one of the regencies in East Java Province, located on the north coast of Java Island. Tuban has various local potentials such as agriculture, plantations, fisheries, and marine resources. Tuban Regency has a long coastline covering several subdistricts, such as Palang, Tuban, Jenu, Tambakboyo, and Bancar. According to the 2020 Performance Report of the Tuban Regency Fisheries Service (LKjIP), the total fishery production increased from 53,677.36 tons in 2018 to 58,608.75 tons in 2019 and then to 63,311.93 tons in 2020. Although the production value is relatively high, limited marketing patterns prevent the community from reaping the maximum benefits. The majority of fishermen only sell raw shrimp to collectors who then manage distribution and determine market prices. This results in fishermen having very little bargaining power, and the community does not obtain added value from post-harvest processes, such as processing or packaging shrimp-based products. Empowerment efforts through aquaculture development are a strategic step. This program will not only provide new skills to the community but also open up home business opportunities and promote collective and sustainable welfare improvement by collaborating with various parties.